Optimizing Management of Facilities and Infrastructure to Enhance Learning Quality in TK Amanah - Adawiah, Rubiatul; Nabilah, Zuhroh; Anggreni, Rizqiqa Dwi; Wahyuningstya A.P, Sabrina; Aulia, Najma; Sjamsir, Hasbi; Rozie, Fachrul (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
Educational facilities and infrastructure play a central role in establishing effective learning processes in early childhood education institutions. This research aims to examine how the management of facilities and infrastructure is implemented at TK Islam Amanah and to explore optimization strategies that can support the enhancement of learning quality. The method used is a qualitative approach with a case study design. Data was gathered through observation, in-depth interviews, and documentation, involving the school principal and teachers as key informants. The findings indicate that the management of facilities and infrastructure at TK Islam Amanah is reasonably well-executed, although constraints persist in the areas of maintenance and inventory administration. The available learning facilities, such as organized classrooms, outdoor play areas, and Educational Play Tools (APE), support children's cognitive, socio-emotional, and motor development. Teachers demonstrate initiative in utilizing natural materials and recycled goods as alternative learning media. Furthermore, the involvement of the principal, teachers, and parents in maintaining and caring for school facilities is a crucial factor in creating a comfortable, safe learning environment that fosters children's enthusiasm for learning.